The postcard killers - Patterson, James, 1947-; Marklund, Liza, 1962- (Little, Brown and Co., 2010)
NYPD detective Jack Kanon and Swedish reporter Dessie Larsson traverse Europe in hot pursuit of a serial killer, one who sends a postcard before each murder and was responsible for the slayings of Jack's daughter and her boyfriend.